Strategi Mencapai Net Cash Flow Dalam Novel Tantangan Satu Miliar Ciputra Karya Antonius Tanan Dkk - Maria Mecha Sukma Arti Yohana; Selvyana Nurlaily Rahmawati; Eva Dwi Kurniawan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
All business companies need a marketing strategy to achieve the desired target. The novel entitled One Billion Ciputra Challenge discusses business travel and marketing strategies from two groups, namely GAS and GAG. This study aims to determine the marketing strategies carried out by the two groups in obtaining a net cash flow of one billion. The method used is hermeneutics, the study of text interpretation, which allows to provide new interpretations. The results of this study are knowing the marketing strategies of the GAS and GAG groups in obtaining one billion, namely testing target markets, good cooperation between members, daring to make interesting innovations, utilizing relationships and promotion through cooperation with companies or agencies, developing business, persevering and never giving up, daring to make decisions, as well as Conduct good communication and presentations with investors. The conclusion of this study is the existence of a good and maximum marketing strategy in the GAS and GAG groups so that they can obtain the desired net cash flow target of one billion.